Avaliação CAPES: análise do cotidiano de um Programa de Pós-graduação em Educação - Welter, Cristiane Backes (Universidade do Vale do Rio do Sinos, 2007)
This dissertation aims at understanding the implications of CAPES evaluation process in the day-to-day life in an educational graduate program. This research was done because of some different opinions about the validity of a national evaluation and its reflexes in the creation of Brazilian graduate courses. Based on ideas of some theorists such as Moraes, Horta, Bianchetti, Brandão, Sguissardi, Silva Jr, Gentili, Wedge, Morosini, Martins, Hostins, we discuss the relation between the historical Brazilian graduate courses and CAPES evaluation process; educational policies and the neoliberal State evaluation; and the graduate course day-to-day life and the experiences of its characters concerning CAPES evaluation. This research was developed in the Educational Graduate Program, in the Vale do Rio dos Sinos University, using the “Discurso do Sujeito Coletivo” methodology. We have created a questionnaire and have done interviews with the people involved in the program: coordinators, professors and students. Prof
Keywords: avaliação; CAPES; política educacional; pós-graduação; ensino superior; graduate; public politics; evaluation; Ciências Humanas